Individual-tree growth system for even-aged Aleppo pine plantations in Aragón, Spain - RODRÍGUEZ-PUERTA, Francisco; ALONSO PONCE , Rafael; FERNÁNDEZ-TOIRÁN , Luz M.; LIZARRALDE, Iñigo (Forest Systems, 2023)
Aim of study: An individual-tree growth system was developed for Aleppo pine (Pinus halepensis Mill.) plantations. Area of study: Aragón region (Northeast Spain). Material and methods: Two datasets were used: Second and Third Spanish National Forest Inventories (104 plots with 1,678 trees), and ad hoc permanent plots (58 plots with 1720 trees, including 36 dead trees). Individual tree growth system was based on nine models. Different combinations of yield classes, initial stocking rates, thinning parameters, rotation periods, and age at first thinning were evaluated through the three most representative scenarios: timber production; soil conservation and biodiversity enhancement. Main results: The nine models demonstrated a significant explanatory power for the data, with R2 values ranging from 0.71 to 0.99. These findings are consistent with previous research, indicating a strong goodness of fit. Additionally, yield tables were developed for the three prevalent silvicultural scenarios. To enhance usability, all models within the system were seamlessly integrated into a web-based application SIMANFOR. Research highlights: To date, Aleppo pine forest managers in Aragon could only simulate silvicultural scenarios in natural stands. This study provides a new tool for plantations.